Role of Nationalized Banks in Sme Credit: A Study in Theni District - Banu, S.Hasan; Sangeetha, P. (Indian Journal of Marketing, 2008)
Small and Medium Enterprises (SMEs) play a catalytic role in the development of any country. They have always been the engine of growth for every country, in developing as well as in transition economies. In India, they account for a significant proportion of manufacturing, of exports and of employment. SMEs are major contributors to the GDP of the country. This sector in India is the second largest manpower employer after agriculture, and currently contributes 40 per cent of the total Industrial production in the country and over 34 per cent of the national exports. In fact, in terms of socio-economic importance, the total number of SMEs at 11.39 million units is nearly 95 per cent of the Industrial units of the country, while providing employment to nearly 27.13 million people, which is nearly 86 per cent of the total employment in the country.